IMPLEMENTASI TEORI VERBAL LINGUISTIC INTELLIGENCE DAN INTERPERSONAL INTELLIGENCE DALAM PEMBELAJARAN MAHARAT AL-KALAM DAN MAHARAT AL-QIRAAH - Azizah, Nur; Abdul Wahab, Muhbib (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2022)
This research aims to analyse the implementation of method, media, and evaluation of speaking skill and reading skill learning in Arabic learning based on the theory verbal linguistic intelligence and interpersonal intelligence. The method of this research was mixed method with triangulation concuren strategy by collecting quantitative data and qualitative data. The finding indicate that the learning of speaking skill and reading skill in learning Arabic at state Islamic Senior High School 2 and 4 Tanah Datar West Sumatera become very effective with applying the linguistic of theory verbal intelligence and interpersonal intellligence in good impact. Developed with that theory make test result Arabic subject the students are in the high category. The benefits of developing this theory in learning can also be concluded from the result of the questionnaire that have shared to students of states Islamic Senior High School 2 and 4 Tanah Datar West Sumatera. It was shown that maha>rat al-kala>m and maha>rat al-qira>'ah in the high category.